Analisis Kualitas Air Tanah berdasarkan Parameter Mikrobiologi (Studi Kasus: Kapanewon Ngaglik, Yogyakarta) - Annisa Nur Lathifah; David Sanjaya; Widodo Brontowiyono (Fakultas Teknik, 2023)
Yogyakarta, Indonesia, has various municipal wastewater treatment (IPAL) facilities; however, only 40% are operational. The study examines how IPAL affects groundwater quality and identifies its causes. Ngaglik, one of three province districts with the largest IPAL number and population density, is the research site. This study only measures microbiological groundwater quality based on Total coliforms and Eschericia coli, according to APHA 2017. Inverse distance weighing (IDW) maps microbiological groundwater quality. The results of the study showed that the observed area had Total Coliform values of 0–170 MPN/100 ml and Escherichia coli concentrations of 0–7. Eleven of the twelve test samples met Permenkes drinking water quality requirements No. 492/Menkes/Per/IV/2010 and PerGub DIY No. 20 of 2008. Seven E. coli concentration measurements exceeded drinkable water requirements. This study showed that E. coli bacteria may have infiltrated groundwater near the sample site. The incident was the first sign that Kapanewon Ngaglik Municipal IPAL was malfunctioning. This data should help assess and improve the effectiveness of the municipal IPAL at the study site and other local IPALs.